Mass vaccination : citizens' bodies and state power in modern China - Brazelton, Mary Augusta, 1986- (Studies of the Weatherhead East Asian Institute, Columbia University., 2019)
"This book reveals that the mass vaccination campaigns that eradicated smallpox and controlled other infectious diseases in China had a longer history, rooted in the work of researchers in China's southwest hinterlands during the Second Sino-Japanese War, and provided a means for the state to develop new forms of control and engagement with its citizens"--